The Impact of The Implementation of The Pedagogic Competency of Teachers of Akidah Akhlak in The Achievement of Student Learning Outcomes - Farida Farida; Mesiono Mesiono; Nur Isnaini Albanjari; M Fajri Syahroni Siregar (At-Tarbiyat, 2021)
Abstract This study discusses student learning outcomes which are only devoted to student learning outcomes in the Akidah Akhlak subject. Based on the learning outcomes of MAN 3 Langkat students, there are still some who have not reached the KKM 85. The pedagogical competencies possessed by Akidah Akhlak teachers at MAN 3 Langkat already have educational qualifications and educational backgrounds in accordance with their field of work. Teachers are also able to fully understand the students. The development of a pedagogical competency curriculum based on implementation planning, evaluation of learning outcomes and the development of student potential is carried out by Akidah Akhlak teachers who have been implemented at MAN 3 Langkat. and utilize technology-based learning media. The impact of the implementation of teacher pedagogic competence in learning is the basis for Akidah Akhlak teachers to diagnose learning difficulties and improve the learning process for students..